Transcriptomics Analysis of Apple Leaves in Response to Alternaria alternata Apple Pathotype Infection - Zhu, Longming; Ni, Weichen; Liu, Shuai; Cai, Binhua; Xing, Han; Wang, Sanhong (Frontiers in Plant Science, 2017)
Alternaria blotch disease of apple (Malus×domestica Borkh.), caused by the apple pathotype of Alternaria alternata, is one of the most serious fungal diseases to affect apples. To develop an understanding of how apples respond to A. alternata apple pathotype (AAAP) infection, we examined the host transcript accumulation over the period between 0 hours and 72 hours post AAAP inoculation. Large-scale gene expression analysis was conducted of the compatible interactions between ‘Starking Delicious’ apple cultivar and AAAP using RNA-Seq and digital gene expression (DGE) profiling methods. Our results show that a total of 9,080 differentially expressed genes (DEGs) were detected (> 2 fold and FDR < 0.001) by RNA-Seq. During the early phase of infection, 12 hours post inoculation (HPI), AAAP exhibited limited fungal development and little change in the transcript accumulation status (950 DEGs). During the intermediate phase of infection, the period between 18 HPI and 36 HPI, increased fungal development, active infection, and increased transcript accumulation were detected (4,111and 3,838 DEGs detected at each time point, respectively). The majority of DEGs were detected by 72 HPI, suggesting that this is an important time point in the response of apples’ AAAP infection. Subsequent gene ontology (GO) and pathway enrichment analyses showed that DEGs are predominately involved in biological processes and metabolic pathways; results showed that almost gene associated with photosynthesis, oxidation-reduction were down-regulated, while transcription factors (i.e., WRKY, MYB, NAC and Hsf) and DEGs involved in cell wall modification, defense signaling, the synthesis of defense-related metabolites, including pathogenesis-related (PRs) genes and phenylpropanoid/cyanoamino acid /flavonoid biosynthesis, were activated during this process. Our study also suggested that the cell wall defensive vulnerability and the down-regulation of most PRs and HSP70s in ‘Starking Delicious’ following AAAP infection might interpret its susceptible to AAAP.